2008
DOI: 10.1097/ccm.0b013e3181653041
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive performance after cardiopulmonary resuscitation in pigs

Abstract: Neurocognitive testing is feasible in this setting. Performance worsens with increasing ischemia time and is structurally associated with alterations in the caudate nucleus and the putamen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…A similar pattern was found in the pig cardiac arrest animal model by Michael Fries et al 14 and has also been shown in clinical practice. 15 CPR before defibrillation does not improve patient outcomes if ambulance response times are Ͻ5 minutes but with longer response times CPR before defibrillation is beneficial.…”
Section: Discussionsupporting
confidence: 59%
“…A similar pattern was found in the pig cardiac arrest animal model by Michael Fries et al 14 and has also been shown in clinical practice. 15 CPR before defibrillation does not improve patient outcomes if ambulance response times are Ͻ5 minutes but with longer response times CPR before defibrillation is beneficial.…”
Section: Discussionsupporting
confidence: 59%
“…A large-animal model of CA and cardiopulmonary resuscitation (CPR) was employed, as has been previously described (18,19,(24)(25)(26). Fifteen male domestic pigs, 4 months of age, were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to conventional hematoxylin and eosin staining, immunohistochemical reactions were used to visualize reactive astrogliosis (polyclonal rabbit anti-glial fibrillary acidic protein), microglial activation (monoclonal mouse CD 68), and the perivascular inflammatory response (monoclonal mouse myeloid/ histiocyte antigen; monoclonal mouse CD 45; all from DakoCytomation Denmark A/S, Glostrup, Denmark). An experienced neuropathologist (KWN), who was blinded to the treatment of the animals, graded the degrees of histopathological alteration, as has been previously reported (18,26). Briefly, for each region of interest, the proportion of neurons with hypereosinophilia, shrunken cytoplasm, and pyknotic nuclei (which are indicative of ischemically induced necrotic damage) was graded into five categories (1 5 0%-10%, 2 5 10%-20%, 3 5 20%-50%, 4 5 50%-80%, and 5 5 80%-100%).…”
Section: Neurohistopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…45 Adicionalmente, a administração de xénon durante a ressuscitação cardiorrespiratória num modelo experimental de paragem cardíaca induzida no suíno, condiciona não só uma menor área de necrose neuronal e atenuação da inflamação perivascular mas também menor disfunção neurocognitiva após ressuscitação Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com cardiopulmonar. 46 A administração de xénon também parece ser benéfi-ca mesmo quando a isquemia já ocorreu, porque parte da lesão pós-enfarte decorre nas zonas de penumbra, zonas viáveis mas em risco de necrose no período que se segue à isquemia aguda. 47 O xénon melhorará a viabilidade destas zonas, conforme já demonstrado em estudos aleatorizados de modelos animais.…”
Section: Sistema Nervosounclassified